Bina'u al-Qasidah Lada al-Sya’ir Usman Abdullah Yahya: Dirasah Tahliliyah Adabiyah - Muhammad, Muhammad Tijjani (Dzil Majaz: Journal of Arabic Literature, 2024)
The poem in Arabic literature from antiquity has its own structure make the poets and critics made this structure basis of their works and the Arabic poem is composed of several sections so the first line of the poem is the introduction. This study uses a qualitative approach with the method used being a Literature Review. Data is collected from various references, both from primary and secondary books, as well as from related articles. Then get rid, to the conclusion for whom he composed poetry the ancient poets adhered  to it and the later critics adhered to it. and this article deals with the historical bag ground of the poet Usman Abdullahi Yahya as its touched on the structure of poems to reach the purpose deserved goal and achieve what he hoped for in the poems